Analisis Pengukuran Kinerja Dengan Metode Balance Scorecard Di PD.BPR.BKK Karangmalang (Periode Tahun 2012-2014) - Adinugroho, Subekti Satrio; , Dra. Mujiyati, M.Si (2016)
The purpose of this study was to measure the performance of PD BPR BKK Karangmalang using performance measurement concept that not only measures of financial performance but also non-financial Balanced Scorecard which includes financial perspective, customer perspective, internal business perspective, and learning and growth perspective. Using the Balanced Scorecard BKK Karangmalang expected to develop financial and non financial aspects in the assessment of the performance, so expect BKK Karangmalang to become an institution can give satisfaction to the customers. This study uses the case study method possible to retrieve data for 3 years, from 2012 to 2014 year. This study is intended to obtain data relating to the company's performance measurement using the Balanced Scorecard concept. The sample in the study was 30 BKK Karangmalang employees and customers, while for sampling using simple random sampling method. The results of this study showed that the overall performance of PD BPR BKK Karangmalang in good enough position viewed from four perspectives of the Balanced Scorecard.